2022
DOI: 10.1021/acs.macromol.2c00092
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Block Copolymers to Understand Water Vaporization Enthalpy Reduction in Uniform Pores

Abstract: Solar desalination, a technique converting solar irradiation to heat for evaporating saltwater and generating freshwater, has garnered much attention because of the evergrowing global demand for potable water. Herein, we utilize block copolymer-based porous carbon fibers with well-controlled porous structures to investigate the latent heat reduction in mesopores and micropores. The porous carbon fibers achieve high energy efficiencies and solar desalination rates up to 3.8 kg m −2 h −1 under 1 sun irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The evaporation enthalpy of the water in the micro‐capillaries of SDP yarn is much smaller than that of bulk water as the capillary size decreases (Figure S28 and Table S2, Supporting Information), which is consistent with Thomson's equation. [ 22 ] However, much lower water content is not beneficial to high evaporation. Thus, precise control of the water content and the water state in the yarn is crucial to designing the fabric‐based SSG with optimal performance.…”
Section: Resultsmentioning
confidence: 99%
“…The evaporation enthalpy of the water in the micro‐capillaries of SDP yarn is much smaller than that of bulk water as the capillary size decreases (Figure S28 and Table S2, Supporting Information), which is consistent with Thomson's equation. [ 22 ] However, much lower water content is not beneficial to high evaporation. Thus, precise control of the water content and the water state in the yarn is crucial to designing the fabric‐based SSG with optimal performance.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the ion sorption on porous carbon fibers follows pseudo-second-order kinetics, and the analysis using the Weber–Morris model confirms that ion diffusion is not a limiting step in the ion sorption and removal process . The same concept applies to treating other contaminants such as dyes, volatile organic chemicals (VOCs), heavy metals, rare earth elements, and toxins. The unique light-absorption capability of porous carbon fibers can potentially enable solar energy for water treatment and contaminant removal . The evaporation of water molecules within the interconnected mesopores shows reduced evaporation enthalpy and likely changes the evaporation behaviors of other molecules.…”
Section: Case Studies Of Applicationsmentioning
confidence: 85%
“…123−125 The unique light-absorption capability of porous carbon fibers can potentially enable solar energy for water treatment and contaminant removal. 126 The evaporation of water molecules within the interconnected mesopores shows reduced evaporation enthalpy 126 and likely changes the evaporation behaviors of other molecules.…”
Section: ■ Precursors For Porous Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…On account of the large body of seawater, desalination is considered a promising solution. , In light of the low cost of solar irradiation, solar desalination represents an attractive strategy, complementing reverse osmosis, vacuum-enhanced evaporation–condensation, and capacitive desalination that require expensive forms of energy (e.g., pressure or electricity) and have a high environmental impact . Recently, many materials have shown the capability of solar desalination, including plasmonic nanostructures, polymer gels, porous carbon fibers, graphene, , graphene oxide, , graphene/alginate hydrogel, carbon black, and carbon foams in suspension, floating, , or contactless mode. However, compared to Nature’s uncanny craftsmanship, we must deepen our understanding of water transport, confinement, and vaporization to build systems on par with or better than biological systems.…”
mentioning
confidence: 99%